2017
DOI: 10.1155/2017/2410504
|View full text |Cite
|
Sign up to set email alerts
|

Nature and Evolution of the Ore-Forming Fluids from Nanmushu Carbonate-Hosted Zn-Pb Deposit in the Mayuan District, Shaanxi Province, Southwest China

Abstract: The Nanmushu carbonate-hosted Zn-Pb deposit is located in the Mayuan district of Shaanxi Province, a newly discovered metallogenic district next to the Sichuan Basin, in the northern margin of the Yangtze Block, which is the largest and the only one that is currently mined in this district. The 34 S values of sulfides are characterized by positive values with a peak around +18‰, and the reduced sulfur may have derived from reduction of SO 4 2− from paleoseawater or evaporitic sulfates that have possibly been l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
(71 reference statements)
0
12
0
Order By: Relevance
“…The close association of CO 2 ‐rich inclusions and H 2 O‐rich inclusions in groups and along the same trail suggests further the presence of fluid immiscibility. Numerous studies have shown that fluid mixing and fluid immiscibility are the dominant mechanisms for the precipitation of Cu (Xiong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The close association of CO 2 ‐rich inclusions and H 2 O‐rich inclusions in groups and along the same trail suggests further the presence of fluid immiscibility. Numerous studies have shown that fluid mixing and fluid immiscibility are the dominant mechanisms for the precipitation of Cu (Xiong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In order to get the exact microthermometric data for each hydrothermal stage, the primary fluid inclusion assemblages (FIAs) were studied. The primary FIs are formed as isolated, in groups, or sometimes along crystal growth zones [39,40], and FIAs represent the contemporaneous entrapment in a hydrothermal stage [41,42]. Secondary FIs occurring in microfractures and transgranular trails are not measured in this study.…”
Section: Methodsmentioning
confidence: 99%
“…As for the geologic position coherency, MVT-type Pb-Zn ore deposits mainly occurs in the carbonate breccia layer, which also coincides with some gas/oil reservoirs. Notably, the layer has high porosity and permeability, providing a good reservoir space and favorable trap conditions [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%